Twelve Pilates sessions improve muscle function but not cardiac autonomic modulation of sedentary patients with low-back pain. - Sakabe, Daniel Iwai; Sakabe, Fabiana Forti; Souza, Ariane Cristina Dias; Guerreiro, Alline Pereira (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction: Physical inactivity is a major risk factor for various pathological conditions in different organic systems, increasing the incidence of musculoskeletal disorders such as low-back pain, as well as the risk for cardiovascular disease. The aim of this study was to evaluate the effect of 12 Pilates sessions on muscle parameters, functional capacity and cardiac autonomic modulation. Methods: 10 volunteers with chronic low-back pain (25.1±5.1 years) underwent 4 assessments before and after training: hamstrings flexibility through photogrammetry; abdominal resistance, through the one minute trunk flexion test; functional capacity through the Roland Morris questionnaire; cardiac autonomic modulation by the RMSSD index of R-R intervals. Mat Pilates training program lasted 12 sessions, each one lasting an hour. Paired student t test, with the level of significance set at 5%, was used to compare data before and after training. Results: Significant improvements (p<0.05) were found on flexibility (58.7±8.2 to 84.1±10.3 degrees on right lower limbs and 57.2±9.1 to 78.5±11.9 on left lower limbs), abdominal resistance (28.3±17.6 to 33.6±16.0 repetitions) and functional capacity (6.2±2.8 to 3.3±1 0 points). Heart rate variability showed no significant change (p = 0.09) after training (RMSSD 37.5±15.0 in pre-training evaluation and 39.0±15.0 in post-training evaluation). Conclusions: We can conclude that the proposed Pilates program was effective in improving muscle and functional parameters, but did not change cardiac autonomic modulation.